Technical and economic viability and nutritional quality of mombasa guinea grass silage production - Fernando Shintate Galindo; Tatiane Beloni; Salatier Buzetti; Marcelo Carvalho Minhoto Teixeira Filho; Elisângela Dupas; Mariana Gaioto Ziolkowski Ludkiewicz (Acta Scientiarum. Agronomy, 2018)
The objective of this study was to evaluate the viability of pasture with high production capacity and the potential for production of silage using different sources and doses of nitrogen (N) by quantifying the productivity of dry matter (DM), some qualitative characteristics, the total cost of production (TC) and total operating cost (TOC) of silage production. The experimental design was randomized block in a factorial scheme with four replications including two sources of nitrogen (urea and ammonium nitrate) and five N doses (0, 50, 100, 150, and 200 kg ha-1 by cutting). The increase in N provided greater DM and crude protein content and reduced the fiber content in neutral detergent. The source of N did not affect the chemical composition, and therefore, it is recommended to use urea due to the ease of acquisition and higher economic return. The production of Mombasa silage can be economically viable due to high DM and crude protein content combined with low production costs. The smallest TC and TOC were obtained in the absence of nitrogen fertilization; however, the proper management of N ensures high productivity in cattle feed with higher total profit when using 100 kg ha-1 N by cutting with ammonium nitrate.